1972
DOI: 10.1007/bf01218493
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of the human pancreatic islets

Abstract: The ultrastructure of the islets of Langerhans was studied in seven human neonates. Out of the five cell types, described by the same authors in the islets of adults, four were also found in the islets of neonates: B cells, A cells, type III ceils and type IV cells. Type III cells were far more numerous in the newborn in contrast with type V cells which were not found. In comparison with the islets of adults those of neonates showed a considerably higher number of pale granules in the B cells and a complete ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Some of the hypoglycemic treatment fetal ␤-cells, however, did have distended RER, but this did not decrease the size, number, or location of secretory granules present. Our measurement of secretory granule diameter is consistent with previously published values for 1-dayold lambs (31) but is smaller than published diameters for the human fetus (33) or neonate (9). There are no published values for secretory granule number, combined area of all secretory granules, or combined area of all mitochondria for fetal sheep ␤-cells for comparison.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Some of the hypoglycemic treatment fetal ␤-cells, however, did have distended RER, but this did not decrease the size, number, or location of secretory granules present. Our measurement of secretory granule diameter is consistent with previously published values for 1-dayold lambs (31) but is smaller than published diameters for the human fetus (33) or neonate (9). There are no published values for secretory granule number, combined area of all secretory granules, or combined area of all mitochondria for fetal sheep ␤-cells for comparison.…”
Section: Discussionsupporting
confidence: 85%
“…Three or four micrographs with at least one ␤-cell in the image were analyzed for each fetus. ␤-Cells were identified by the characteristic appearance of the secretory granules, which contain contents of variable electron density with a surrounding halo (6,9,31,33). In addition, Ͼ90% of the total islet area contained insulin-positive ␤-cells (see RESULTS), facilitating selection of ␤-cells for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted, however, that the human pancreas contains at least two distinct small-granulated islet cell types -the one containing the smallest granules being the PP cell. Of the islet cell types previously described in the human pancreas the type V cell of Deconinck et al [28] seems to correspond best with the PP cell.…”
Section: Discussionmentioning
confidence: 82%
“…Two qualitative studies have demonstrated the presence of somatostatin cells in the human fetus [1,6]. With ultrastructural and histochemical techniques [4,10], it has been shown that the islets of neonates or young infants contain a high proportion of non-insulin and non-glucagon cells, most likely corresponding to somatostatin cells. This has been recently confirmed [15] with an immunofluorescence method.…”
mentioning
confidence: 99%